PERENCANAAN JARINGAN DISTRIBUSI AIR BERSIH DILENGKAPI DENGAN PENETAPAN TITIK DMA (DISTRICT METER AREA) DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Yuliani Yuliani (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
ABSTRACT Tenayan Raya Subdistrict, Pekanbaru has a population of 167,929 people, and a population growth rate of 2.64% (BPS, 2019). The increasing population resulted in the need for clean water also increased. In thisplan there are three aspects studies, namely technical, financial, and institutional aspects. Study of technical aspects to plan the length, diameter of pipes,profile of hydraulics with epanet, as well as the addition of DMA points. Review the financial aspects to find out the feasibility of the. Study of institutional aspects to support PDAM performance improvement program. The results of the study of technical aspects are planned transmission pipe diameter of 1500 mm, length of 2,999.1 m and jaringan main distribution length of 25,557.38 m. Results of financial aspect studies that is a project worth. The results of the study of institutional aspects concluded the concept of strategy that can be used by PDAM Pekanbaru, namely WO (Weakness-Opportunities).